The absence of high-risk human papillomavirus in Czech non-small cell lung cancer cases - Jaworek, Hana; Koudelakova, Vladimira; Slavkovsky, Rastislav; Drabek, Jiri; Hajduch, Marian (Biomedical papers, 2020)
Aims: The purpose of our study was to examine the presence of human papillomavirus (HPV) DNA in Czech patients with non-small cell lung cancer (NSCLC). Methods: A highly sensitive quantitative polymerase chain reaction (qPCR) detecting the E6 gene of HPV16, 18, 31, and 56 was designed. The limit of detection was assessed using serial dilutions of HPV-positive plasmids. The qPCR was validated on a set of 402 cervical swabs where the qPCR, Cobas, and PapilloCheck methods were tested in parallel. Finally, qPCR was used for HPV detection in a set of 80 patients with primary NSCLC, both from formalin-fixed paraffin-embedded (FFPE) and fresh frozen (FF) tissue samples. Results: The qPCR method was able to reliably detect at least 4 copies of the E6 gene per reaction in HPV16, 18, and 31, and 40 copies per reaction in HPV56. The sensitivity and specificity of the qPCR were 75.6-99.3% and 63.9-100% respectively, depending on the HPV genotype and reference method used. HPV DNA was not detected in the FFPE and FF samples from the set of 80 NSCLC patients. Conclusion: No hrHPV DNA was found in primary NSCLC tumors from a Czech population.
Keywords: human papillomavirus; non-small cell lung cancer; PCR; HPV16; HPV18